Advances in Spatial Databases : 4th International Symposium, SSD'95 Portland, ME, USA, August 6-9, 1995 Proceedings - Egenhofer, Max J.; Herring, John R. (Berlin, Heidelberg : Springer-Verlag, 1995)
This book presents the proceedings of the 4th International Symposium on large Spatial Databases, SSD '95, held in Portland, Maine, USA in August 1995. The 23 refereed full papers presented were selected from more than 60 submissions and describe the state-of-the-art in the expanding field of large spatial databases, with a certain emphasis on an upcoming new generation of spatial database management systems. The volume is organized in sections on spatial data models, spatial data mining, spatial query processing, multiple representations, open GIS, geo-algorithms, reasoning about spatial relations, spatial joins, and benchmarks.
Lossless representation of topological spatial data -- On the desirability and limitations of linear spatial database models -- The quad view data structure -- a representation for planar subdivisions -- Discovery of spatial association rules in geographic information databases -- Knowledge discovery in large spatial databases: Focusing techniques for efficient class identification -- Ranking in spatial databases -- Optimal redundancy in spatial database systems -- Accessing geographical metafiles through a database storage system -- Extending a spatial access structure to support additional standard attributes -- Towards a formal model for multiresolution spatial maps -- Multi-Scale partitions: Application to spatial and statistical databases -- Specifying open GIS with functional languages -- Load-balancing in high performance GIS: Declustering polygonal maps -- Implementation of the ROSE algebra: Efficient algorithms for realm-based spatial data types -- A 3D molecular surface representation supporting neighborhood queries -- An inferencing language for automated spatial reasoning about graphic entities -- Inferences from combined knowledge about topology and directions -- 2D projection interval relationships: A symbolic representation of spatial relationships -- Topological relations between discrete regions -- Generating seeded trees from data sets -- Spatial join strategies in distributed spatial DBMS -- Comparison and benchmarks for import of VPF geographic data from object-oriented and relational database files -- Compressing Elevation Data.
Keywords: Computer science; Electronic Data Processing; Informatique; Computer science